Effect of Top-Region Area of Flat-Top Pyramid Patterned Sapphire Substrate on the Optoelectronic Performance of GaN-Based Light-Emitting Diodes. (11th August 2016) - Hsueh, Hsu-Hung; Ou, Sin-Liang; Peng, Yu-Che; Cheng, Chiao-Yang; Wuu, Dong-Sing; Horng, Ray-Hua
Abstract : The flat-top pyramid patterned sapphire substrates (FTP-PSSs) have been prepared for the growth of GaN epilayers and the fabrication of lateral-type light-emitting diodes (LEDs) with an emission wavelength of approximately 470 nm. Three kinds of FTP-PSSs, which were denoted as FTP-PSS-A, FTP-PSS-B, and FTP-PSS-C, respectively, were formed through the sequential wet etching processes. The diameters of circle areas on the top regions of these three FTP-PSSs were 1, 2, and 3 μ m, respectively. Based on the X-ray diffraction results, the full-width at half-maximum values of rocking curves at (002) plane for the GaN epilayers grown on conventional sapphire substrate (CSS), FTP-PSS-A, FTP-PSS-B, and FTP-PSS-C were 412, 238, 346, and 357 arcsec, while these values at (102) plane were 593, 327, 352, and 372 arcsec, respectively. The SpeCLED-Ratro simulation results reveal that the LED prepared on FTP-PSS-A has the highest light extraction efficiency than that of the other devices. At an injection current of 350 mA, the output powers of LEDs fabricated on CSS, FTP-PSS-A, FTP-PSS-B, and FTP-PSS-C were 157, 254, 241, and 233 mW, respectively. The results indicate that both the crystal quality of GaN epilayer and the light extraction of LED can be improved via the use of FTP-PSS, especially for the FTP-PSS-A.